An early analysis of the World Bank’s Pandemic Fund: a new fund for pandemic prevention, preparedness and response - Boyce, Matthew R.; Sorrell, Erin M.; Standley, Claire J. (BMJ global health, 2023)
In response to shortcomings in epidemic preparedness and response that were revealed by the COVID-19 pandemic, there have been numerous proposals for ways to improve preparedness and response financing. Included among these is the World Bank’s Pandemic Fund, formerly known as the Financial Intermediary Fund for Pandemic Prevention, Preparedness, and Response, which was launched in September 2022. This analysis piece examines the Pandemic Fund, where it fits into ongoing discussions surrounding financing for preparedness and response efforts and discusses emerging apprehensions about the new financing mechanism. Briefly, the Pandemic Fund is not the first time that the World Bank has hosted a financing mechanism to provide support for pandemic response. Notably the Pandemic Emergency Financing Facility (PEF)—which was launched in 2017 and closed in 2021—was criticised for generally failing to realise its potential. However, the Pandemic Fund seems to be addressing several of these critiques by placing a greater emphasis on prevention and preparedness financing, as opposed to response financing. Still, there is an important need for response funding mechanisms, and concerningly, the Pandemic Fund seems to support response efforts in name only. While it is clearly desirable to prepare for and prevent outbreaks for a multitude of reasons, it is also naive to assume that strengthening preparedness capacities will eliminate outbreaks and the need for response financing altogether. Accordingly, there is a need to complement this new financing mechanism with dedicated funding for responding to infectious disease outbreaks and to closely link this response financing with health security frameworks and instruments.